Feasibility and preliminary clinical results of linac-based Stereotactic Body Radiotherapy for spinal metastases using a dedicated contouring and planning system - Giaj-Levra, Niccolò (Radiat Oncol, 2019)
BACKGROUND: Stereotactic radiosurgery (SRS) and stereotactic body radiotherapy (SBRT) are well established local treatment approaches in several cancer settings. Although SBRT is still under investigation for spinal metastases, promising results in terms of a high effectiveness and optimal tolerability have been recently published on this topic. For spinal SBRT, one of the most relevant issues is represented by the inter-observer variability in target definition. Recently, several technological innovations, including specific tools such as multimodality-imaging (computed tomography (CT), magnetic resonance imaging (MRI) and positron emission tomography (PET-CT), automated volumes contouring and planning, could allow clinicians to minimize the uncertainties related to spinal SBRT workflow. Aim of this study is to report the feasibility of the clinical application of a dedicated software (Element®, Brainlab™ Germany) for spinal metastases SBRT. MATERIAL AND METHOD: The patient selection criteria for SBRT in spinal metastases were the following: age > 18 years, diagnosis of spinal metastases (n ≤ 3), life expectancy > 3 months, controlled primary tumor or synchronous diagnosis and Spinal Instability Neoplastic Score (SINS) ≤ 12 points. All radiation target volumes were defined and planned with the support of the dedicated software Elements® (Brainlab™ Germany). Different dose prescription have been used: 12 Gy in single fraction, 12 Gy, 18 Gy, 21 Gy and 24 Gy in 3 fractions. Toxicity was assessed according to the Common Terminology Criteria for Adverse Events (CTCAE) v4.0. SPSS version 20 was used for statistical analysis. RESULTS: From April 2018 to April 2019, 54 spinal metastases in 32 recruited patients were treated with Linac-based SBRT. With a median follow-up of 6 months (range 3–12), local control rates at 6 months and 9 months were 86 and 86%, respectively. No adverse events ≥3 grade were observed. CONCLUSIONS: This preliminary experience shows that with respect to acute toxicity and early clinical response, linac-based using Elements® Spine SRS is a feasible and effective approach.